Determination of Superior Agricultural Commodity Areas Based on Historical Data and Land Suitability - Alfina Zukhrifa; Fadli Irsyad; Delvi Yanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Analysis and identification of superior agricultural commodity areas play a crucial role in determining regions with high potential for agricultural development. This study aims to identify priority agricultural commodities and assess their development potential in Lawang, Matur District, Agam Regency, West Sumatra Province. The research was conducted in several stages. First, superior agricultural commodities were identified using the Location Quotient (LQ) and Shift Share Analysis (SSA) methods. Second, the potential development areas for these commodities were determined using the Analytical Hierarchy Process (AHP) and Weighted Linear Combination (WLC) approach, integrated with Geographic Information System (GIS) analysis. The results indicate that the priority agricultural commodities in Nagari Lawang are peanuts for the food crop subsector, shallots for the horticulture subsector, and sugarcane for the plantation subsector. These findings provide valuable information for policymakers and local farmers to optimize land use, enhance agricultural productivity, and support sustainable rural economic development. Furthemore, the methodology used in this study can also be applied to other regions to identify superior agricultural commodities.Keywords: Analytical hierarchy process, Leading commodities, Location quotient, Shift share analysis, Weight linear combination.